Semua berharga di mata Tuhan: Konstruksi nilai spiritual pelayanan gerejawi bagi anak berkebutuhan khusus melalui pembacaan Matius 10:30-31 - Natalia, Desi; Merilyn; Setinawati (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
Children with special needs have characteristics that are not the same as most other children, thus demanding special treatment in carrying out the responsibilities of church ministers. This difference shows that every child is God's special creation, and the church's responsibility to serve them also varies. Some churches accept and are open to the privileges of these children, especially for the development of spirituality and religious religiosity. Still, some churches make them objects for the people around them. This study aims to offer the value of ecclesial service to children with special needs through a reading of Matthew 10:30-31. With a qualitative research approach and using the method of interpretive analysis of scriptural texts, I obtained a foundational value of ecclesial ministry, that is,